2003
DOI: 10.1073/pnas.1936251100
|View full text |Cite
|
Sign up to set email alerts
|

Conformations and dynamics of Ets-1 ETS domain–DNA complexes

Abstract: Molecular dynamics studies have been performed for 3.5 ns on the ETS domain of Ets-1 transcription factor bound to the 14-bp DNA, d(AGTGCCGGAAATGT), comprising the core sequence of high-affinity (GGAA), ETS-GGAA. In like manner, molecular dynamics simulations have been carried out for 3.9 ns on the mutant low-affinity core sequence, GGAG (ETS-GGAG). Analyses of the DNA backbone of ETS-GGAG show conformational interconversions from BI to BII substates. Also, crank shaft motions are noticed at the mutated nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
(37 reference statements)
0
28
0
Order By: Relevance
“…PU.1 is the most sequence-divergent member of the ETS family, a feature that may be correlated with its extensively hydrated protein-DNA interface. "Canonical" ETS-DNA complexes such as Ets-1 (11,12) and GABP␣ (42) feature a higher density of direct protein-to-nucleobase contacts than PU.1. Specific hydration might therefore evolve as compensatory mechanism to replace some of the "missing" anhydrous contacts.…”
Section: Discussionmentioning
confidence: 99%
“…PU.1 is the most sequence-divergent member of the ETS family, a feature that may be correlated with its extensively hydrated protein-DNA interface. "Canonical" ETS-DNA complexes such as Ets-1 (11,12) and GABP␣ (42) feature a higher density of direct protein-to-nucleobase contacts than PU.1. Specific hydration might therefore evolve as compensatory mechanism to replace some of the "missing" anhydrous contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bruice and co-workers reported MD simulation results of Ets-1 bound to two different DNA sequences containing either GGAA or GGAG at the center, to understand how a single protein can differentiate two related DNA sequences. 38,39 They postulated that the binding affinity of Ets for the GGAG sequence is lower because of the alternate hydrogen bonds from Y395 (corresponding to Y66 of Elk) to either A3 or C4 0 , which destabilize the bidentate hydrogen bonds from R341 and R344 to DNA bases G2 and G1, respectively. When bound to a high-affinity site containing GGAA, the movement of Y395 is restricted by the C5 methyl group of T3 0 , which helps immobilize key hydrogen bonding networks.…”
Section: Discussionmentioning
confidence: 99%
“…NMR and X-ray crystallography studies of ETS domains have shown that helix-3 binds in the major groove of the basic DNA sequence [18,19]. ETS binding sites have been identified in the promoter/regulatory regions of over 200 genes and ETS proteins have been estimated to bind between 5 and 15 % of gene promoters, including many housekeeping genes [9].…”
Section: Ets Factors Functional Domainsmentioning
confidence: 99%